Transcatheter Myotomy to Relieve Left Ventricular Outflow Tract Obstruction: The Septal Scoring Along the Midline Endocardium Procedure in Animals. (5th April 2022) - Khan, Jaffar M.; Bruce, Christopher G.; Greenbaum, Adam B.; Babaliaros, Vasilis C.; Jaimes, Andrea E.; Schenke, William H.; Ramasawmy, Rajiv; Seemann, Felicia; Herzka, Daniel A.; Rogers, Toby; Eckhaus, Michael A.; Campbell-Washburn, Adrienne; et al.
Abstract : Background: Left ventricular outflow tract obstruction complicates hypertrophic cardiomyopathy and transcatheter mitral valve replacement. Septal reduction therapies including surgical myectomy and alcohol septal ablation are limited by surgical morbidity or coronary anatomy and high pacemaker rates, respectively. We developed a novel transcatheter procedure, mimicking surgical myotomy, called Septal Scoring Along the Midline Endocardium (SESAME). Methods: SESAME was performed in 5 naive pigs and 5 pigs with percutaneous aortic banding–induced left ventricular hypertrophy. Fluoroscopy and intracardiac echocardiography guided the procedures. Coronary guiding catheters and guidewires were used to mechanically enter the basal interventricular septum. Imparting a tip bend to the guidewire enabled intramyocardial navigation with multiple df . The guidewire trajectory determined the geometry of SESAME myotomy. The myocardium was lacerated using transcatheter electrosurgery. Cardiac function and tissue characteristics were assessed by cardiac magnetic resonance at baseline, postprocedure, and at 7- or 30-day follow-up. Results: SESAME myotomy along the intended trajectory was achieved in all animals. The myocardium splayed after laceration, increasing left ventricular outflow tract area (753 to 854 mm 2, P =0.008). Two naive pigs developed ventricular septal defects due to excessively deep lacerations in thin baseline septa. No hypertrophy model pig, with increased septal thickness and left ventricular mass compared with naive pigs, developed ventricular septal defects. One animal developed left axis deviation on ECG but no higher conduction block was seen in any animal. Coronary artery branches were intact on angiography with no infarction on cardiac magnetic resonance late gadolinium imaging. Cardiac magnetic resonance chamber volumes, function, flow, and global strain were preserved. No myocardial edema was evident on cardiac magnetic resonance T1 mapping. Conclusions: This preclinical study demonstrated feasibility of SESAME, a novel transcatheter myotomy to relieve left ventricular outflow tract obstruction. This percutaneous procedure using available devices, with a safe surgical precedent, is readily translatable into patients.